Protein disulfide isomerase and glutathione are alternative substrates in the one Cys catalytic cycle of glutathione peroxidase 7 - Bosello-Travain, Valentina; Conrad, Marcus; Cozza, Giorgio; Negro, Alessandro; Quartesan, Silvia; Rossetto, Monica; Roveri, Antonella; Toppo, Stefano; Ursini, Fulvio; Zaccarin, Mattia; Maiorino, Matilde (Biochimica et biophysica acta, 2013)
Mammalian GPx7 is a monomeric glutathione peroxidase of the endoplasmic reticulum (ER), containing a Cys redox center (CysGPx). Although containing a peroxidatic Cys (CP) it lacks the resolving Cys (CR), that confers fast reactivity with thioredoxin (Trx) or related proteins to most other CysGPxs. Reducing substrate specificity and mechanism were addressed by steady-state kinetic analysis of wild type or mutated mouse GPx7. The enzymes were heterologously expressed as a synuclein fusion to overcome limited expression. Phospholipid hydroperoxide was the oxidizing substrate. Enzyme–substrate and protein–protein interaction were analyzed by molecular docking and surface plasmon resonance analysis. Oxidation of the CP is fast (k+1>103M−1s−1), however the rate of reduction by GSH is slow (k′+2=12.6M−1s−1) even though molecular docking indicates a strong GSH–GPx7 interaction. Instead, the oxidized CP can be reduced at a fast rate by human protein disulfide isomerase (HsPDI) (k+1>103M−1s−1), but not by Trx. By surface plasmon resonance analysis, a KD=5.2μM was calculated for PDI–GPx7 complex. Participation of an alternative non-canonical CR in the peroxidatic reaction was ruled out. Specific activity measurements in the presence of physiological reducing substrate concentration, suggest substrate competition in vivo. GPx7 is an unusual CysGPx catalyzing the peroxidatic cycle by a one Cys mechanism in which GSH and PDI are alternative substrates. In the ER, the emerging physiological role of GPx7 is oxidation of PDI, modulated by the amount of GSH. ► The ER contains GPx7, a Cys-glutathione peroxidase missing a resolving Cys. ► The catalytic Cys is oxidized at a fast rate by hydroperoxides. ► GSH binds to the active site, but the release of the reduced enzyme is slow. ► GPx7 is competent for a fast oxidation of PDI. ► Kinetics suggest that physiological GSH regulates the oxidation of PDI by GPx7.